WSV152 induces apoptosis and promotes viral replication in Litopenaeus vannamei. Issue 98 (March 2020) - Yan, Muting; Liu, Zhihao; Xu, Kaihang; Wang, Wenjing; Fan, Lanfen; Gong, Han
Abstract: Previous studies have indicated that white spot syndrome virus (WSSV) infection induces apoptosis in many shrimp organs. However, the mechanism by which WSSV causes host apoptosis remains largely unknown. In this study, we demonstrated the function of wsv152, the first mitochondrial protein identified as encoded by WSSV. Glutathione S-transferase pulldown and co-immunoprecipitation analysis revealed that wsv152 interacts with the shrimp mitochondrial protein cytochrome c oxidase 5a (COX5a), a subunit of the COX complex. We also found that wsv152 expression significantly increased the rate of apoptosis, suggesting a role of wsv152 in WSSV-induced apoptosis in shrimp. Knockdown of wsv152 in vivo led to downregulation of several apoptosis-related shrimp genes, including cytochrome c, apoptosis-inducing factor and caspase-3. Suppression of wsv152 also resulted in significant reductions in the number of WSSV genome copies in tissues and in the mortality of WSSV-infected shrimp. Together, these results suggest that wsv152 targets host COX5a and is associated with the expression profiles of apoptosis-related shrimp genes. Wsv152 is likely also involved in WSSV-induced apoptosis, thereby facilitating virus infection and playing a complex role in WSSV pathogenesis. Highlights: Wsv152 interacted with a mitochondria-located protein COX5a. Expression of wsv152 significantly increased the percentage of cell apoptosis. Wsv152 was involved in the expression of CYC, AIF and caspase-3. Wsv152 played a role in WSSV pathogenesis.